Approaches for Supporting and Advancing Faculty at All Stages - Carpenter, Russell; Dvorak, Kevin; Head, Karen J. (The journal of faculty development, 2025)
Faculty development that supports faculty across career stages has become a more significant focus given challenges of faculty engagement and retention efforts in higher education. Based on current research, the authors provide perspectives on faculty development initiatives, efforts, and approaches that support faculty development within and across career stages, interests, and priorities.